THE EFFECT OF INTEREST INCOME GROWTH, CAPITAL STRUCTURE, AND DIGITAL TRANSFORMATION ON FINANCIAL PERFORMANCE WITH COMPANY SIZE AS A MODERATING VARIABLE - Rahmad Ramdani; Nur Ravita Hanun (International Journal of Economic Integration and Regional Competitiveness, 2026)
Objective: This study aims to analyze the influence of interest income growth, capital structure, and digital transformation on financial performance, with company size as a moderating variable. Method: This study uses a quantitative approach with secondary data obtained from the financial statements of banking companies listed on the Indonesia Stock Exchange. The sample was selected based on purposive sampling and analysis using moderated regression. Results: The results show that interest income growth has no effect on financial performance, capital structure has no effect on financial performance, while digital transformation does. In addition, company size weakens the relationship between interest income growth and financial performance, but strengthens the relationship between capital structure and digital transformation on financial performance. Novelty: The findings of this study indicate that the mechanism of utilizing digital technology advances can play a role in influencing a company's financial performance practices.